City structure – the phenomenon of exclusion of space - Marta Szejnfeld, Marta; Kmiecik, Grzegorz; Szymczak, Hanna (European Journal of Sustainable Development, 2014)
A special feature of spaces with urban character is the phenomenon of exclusion, which refers both to the space and the community, causing deformation and the disappearance of the unity of the urban structure as a whole. Spatial segregation processes – resulting from social polarization – causes low–income or marginalized groups lack of access to a high–quality urban space. Excluded spaces have become a constant component of visual reality in which gated communities, guarded buildings, or corporation complexes have divided the urban fabric, and in opposition to the city, are capturing more and more spaces. The result of the appearance of the excluded spaces is the lack of the right to the city for all its inhabitants. Foresaid lack deprives the participant of the possibility of observation and penetration the urban structure, which further deepens the sense of alienation. In such spatial conditions the longing for re–evoking the idea of a sustainable city is born. The essence is therefore an insightful diagnosis of the impact of uncontrolled processes shaping the urban structure deepening segregation and exclusion from the urban space. Keywords: urban transformation, exclusion, inhabitants